Banking for a Better World - Kleiterp, Nanno (Amsterdam University Press, 2017)
When we look at all the challenges facing the world, including inequality, population migration, and climate change, we can see a role for development banking in nearly all of them. But will that role be played for good or ill? This book brings together two people who collectively draw on their forty-five years of experience in that world to argue that development banking can-and must-play a constructive role. We only need to read the news to find public outrage at tales of short-sighted greed in the financial world. But what happens when banks invest in long-term sustainability? Readers will find a fascinating example in the journey of the Dutch development bank FMO. At times global in perspective, at other moments intimately personal, Banking for a Better World interweaves candid anecdotes with development history, as well as banking lessons with client interviews, to deliver a powerful argument for a business model that generates profit through impact, and impact through profit. This is an important and accessible must-read for anyone involved in banking, business, policy making, and civil society as a whole. Banking for a Better World challenges us to start finding overlaps between our own lives and global issues and to bridge the distance between our personal needs and those of our planet.